The Effect of Earnings Management on the Capital Structure Analytical Study of the Iraqi Stock Market - Ali Jassim Muhammad Anad; Shatha Abdul Hussein Jaber (Journal of Madenat Alelem University College, 2022)
The study aimed to define the nature of profit management and the motives for its adoption and strategies, and the most prominent factors in a way that helps in enhancing information for decision makers, and to determine whether the practice of the profit management phenomenon affects the capital structure of the research sample companies. The modified Jones model (1995) was relied on in order to measure profit management and the (CAMP) model to measure the weighted average of the capital structure. The research community consisted of all companies listed on the Iraqi Stock Exchange for the period (2010-2019), and the research sample included (26) companies that met the conditions of companies, and the study found that (53%) of the companies in the research sample had practiced profit management throughout the research period (2010-2019), while the remaining companies were practicing it for varying periods. Profits in the cost of capital structure in the research sample companies, as the results showed a weak and significant inverse relationship between the cost of capital structure and the practice of profit management for companies.As for the most important recommendations that were reached, the company management should realize the risks that may arise when practicing profit management on the performance and market value of the company. Investors and analysts should also realize and analyze the difference between the income statement, which is prepared according to the accrual system, and the cash flow statement, as it is prepared on a cash basis and cannot be manipulated.